The Safety and Efficacy of Gastric Fundal Variceal Obliteration Using N-Butyl-2-Cyanoacrylate; The Experience of a Single Canadian Tertiary Care Centre - Mosli, Mahmoud H. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND/AIM: Bleeding from Gastric Varices (GV) is not only life threatening, but also leads to many hospitalizations, contributes to morbidity and is resource intensive. GV are difficult to diagnose and their treatment can be challenging due to their location and complex structure. To assess the safety and efficacy of endoscopic gastric fundal variceal gluing using periodic endoscopic injections of N-butyl-2-cyanoacylate (NBCA) and to assess the utility of endoscopic ultrasound (EUS) in assessing for the eradication of GV post-NBCA treatment. MATERIALS AND METHODS: Analysis of prospectively collected data of a cohort of patients with GV who underwent periodic endoscopic variceal gluing from 2005 to 2011. Outcomes included success of GV obliteration, incidence of rebleeding, complications from the procedure, and analysis of factors that might predict GV rebleeding. The success of GV eradication was assessed by both EUS and direct endoscopy. RESULTS: The cohort consisted of 29 consecutive patients that had undergone NBCA injection for GV. The mean age was 60.8 years standard deviations (SD 13.3, range 20-81). The average follow-up was 28 months (SD 19.61, range 1-64) and the most common cause for GV was alcoholic liver cirrhosis (34.48%). A total of 91 sessions of NBCA injections were carried out for 29 patients (average of 3.14 sessions/patient, SD 1.79, range 1-8) with a total of 124 injections applied (average of 4.28 injections/patient, SD 3.09, range 1-13). 24 patients were treated for previously documented GV bleeding while five were treated for primary prevention. Overall, 79% of patients were free of rebleeding once three sessions of histoacryl(®) injection were completed. None of the patients treated for primary prevention developed bleeding during follow-up. 11 of the 24 patients (46%) with previous bleeding however had rebleeding. 4/11 (36%) patients had GV rebleeding while awaiting scheduled additional NBCA sessions. 19/29 (60%) patients had complete eradication of GV, 11/19 (58%) documented by endoscopic assessment alone, 4/19 (21%) by EUS alone and 4/19 (21%) by both techniques. Two of the 11 (18%) patients that had rebleeding had recurrence of GV bleeding after documented eradication by EUS compared to 5/11 (45%) patients documented eradication by endoscopic assessment and 2/11 (18%) patients that had rebleeding after documented eradication by both modalities. Twenty five patients in total had documented residual GV by EUS (14, 56%), direct endoscopic assessment (18, 72%) or both modalities (9, 36%), two of which developed recurrent bleeding (13%). No immediate or long-term complications of NBCA injection occurred, nor any related endoscopic complications were reported in any of these cases during the time of follow-up. CONCLUSION: NBCA injection of GV is a safe and successful therapeutic intervention. A minimum of three endoscopic sessions is required to significantly decrease the risk of bleeding/rebleeding. In this small sample of patients, neither EUS nor direct endoscopic assessment was reliable in predicting the recurrence of GV bleeding.